The Reality Of The Globalizing World And The Proactive Dimension Of The Human World Of “Boundless Careers” - Agnieszka Cybal-Michalska (PEOPLE: International Journal of Social Sciences, 2025)
Global transformations of the modern world, which have a multidimensional nature, and which almost all aspects of social existence are subject to, seem to be inescapable and their complexity difficult to grasp. Globalisation tendencies in the world deprived the modern society of stability which was characteristic for the modern epoch of industrial society. However, dialectical nature of globalisation determines development of societies’ ability to anticipate dangers and coping with them at individual, social and global levels. New chances and new possibilities emerge in micro- and macro-scale, but there are also fears and concerns, which define the contours of the society of tomorrow. Quality specification of new transformations in relations between globality and locality, society and unit, and their interconnections, is by no means irrelevant to multicontextual changes in the world of work. These changes make new demands on employees. The vision implies a completely new perception of reality, ways of interpreting the worlds, and new quality of judgements on the condition of modern world – including a man as the “manager” of his own career. The most important, subjective and internal meaning of career must be correlated with its external traits. Therefore, personal meaning, despite being influenced by social categories to which the individual belongs, cannot be derived only from these categories. It is also important to consider orientation categories which are understood as individual tendencies characterised by lasting expressiveness. Coexistence of cognitive, normative, emotional and behavioural components is accompanied by an objective which relates to achievement of what, according to the individual, is worthy of desire in career. Career commitment is characterised by development of personal career objectives, devotion to these objectives, identification with them and commitment to them. Changes in the world of “boundless” careers make the problem of entity’s proactivity that is proactive behavior of the entity in career, topical. The distinctive feature of proactive planning and career management is awareness of being an entity which follows the desired direction and influences the surrounding reality by initiating changes. Proactive attitude of an entity is reflected in the processes of pursuit and achieving objectives which, as a result, make the entity a creator of reality rather than its forecaster. Proactive persons explore the environment, look for the possibilities of change, go beyond the limitations imposed by the situation, directing it in a way which allows to derive all benefits brought by reshaping the situation. Commitment to an internally defined career may be a significant source of shaping entity’s (professional) identity, which seems to be indispensable for the entity’s career progress in the world of “boundless” careers in the reality of a globalising world.